2015
DOI: 10.1007/s00134-015-4111-8
|View full text |Cite
|
Sign up to set email alerts
|

Does high-pressure, high-frequency oscillation shake the foundations of lung protection?

Abstract: There is a strong temptation to take a reductionist approach that would permit us to assign a single mechanistic cause for ventilation-induced lung injury (VILI) and thereby identify a simple bedside intervention to avoid its consequences. However, convincing investigations have uncovered at least three ways in which adverse tidal cycling pressures may injure the lung: (1) over distension of already inflated alveoli, with cellular distortion, epithelial wounding, and capillary stress fracture [1]; (2) tidal op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Therefore, whatever maneuver reduces the applied mechanical power (such as reducing tidal volume), driving pressure or respiratory rate will reduce the probability of VILI. The disappointing results of high-frequency oscillation studies [ 36 , 37 ] can be considered under the aspect of power: even small tidal excursions, multiplied by the driving pressure and by the hundreds of cycles per minute, may generate an intolerable mechanical load. For a given mechanical load, the risk of VILI decreases if the lung is made more homogeneous, thereby reducing the presence of stress risers [ 31 , 32 ].…”
mentioning
confidence: 99%
“…Therefore, whatever maneuver reduces the applied mechanical power (such as reducing tidal volume), driving pressure or respiratory rate will reduce the probability of VILI. The disappointing results of high-frequency oscillation studies [ 36 , 37 ] can be considered under the aspect of power: even small tidal excursions, multiplied by the driving pressure and by the hundreds of cycles per minute, may generate an intolerable mechanical load. For a given mechanical load, the risk of VILI decreases if the lung is made more homogeneous, thereby reducing the presence of stress risers [ 31 , 32 ].…”
mentioning
confidence: 99%
“…The approach of using low frequencies in patients with restrictive respiratory-system conditions may increase the risk of barotrauma and/or rheotrauma, due to poor downstream oscillation pressure-wave damping. 26,27 In the more compliant lung (eg, during weaning from HFOV, when more effective spontaneous breathing efforts by the patient can be allowed), oscillation pressure-wave damping becomes much more important because it reduces the risk of barotrauma. Therefore, lower frequencies can be used, and oscillation pressure amplitudes at the airway opening can be further reduced while maintaining the same ventilation efficiency.…”
Section: Influence Of Frequencymentioning
confidence: 99%
“…High-frequency oscillation ventilation (HFOV) seems the perfect embodiment of the “open lung theory” as it suggests extremely low tidal volumes combined with very high mean airway pressures. With disappointment clinical trials showed that the application of HFOV was associated with a decreased survival [ 1 ]. The culprit has not been identified, and a possible cause is the effect of increased intrathoracic pressures on the right ventricle and very high intrathoracic pressures which act as an obstacle to blood flow [ 1 ].…”
mentioning
confidence: 99%
“…With disappointment clinical trials showed that the application of HFOV was associated with a decreased survival [ 1 ]. The culprit has not been identified, and a possible cause is the effect of increased intrathoracic pressures on the right ventricle and very high intrathoracic pressures which act as an obstacle to blood flow [ 1 ]. When a positive pressure is applied to the respiratory system, it is spent in part to inflate the lung and in part to inflate the chest wall.…”
mentioning
confidence: 99%
See 1 more Smart Citation